Phi Class of Glutathione S-transferase Gene Superfamily Widely Exists in Nonplant Taxonomic Groups. (January 2016) - Munyampundu, Jean-Pierre; Xu, You-Ping; Cai, Xin-Zhong
Glutathione S-transferases (GSTs) constitute a superfamily of enzymes involved in detoxification of noxious compounds and protection against oxidative damage. GST class Phi (GSTF), one of the important classes of plant GSTs, has long been considered as plant specific but was recently found in basidiomycete fungi. However, the range of nonplant taxonomic groups containing GSTFs remains unknown. In this study, the distribution and phylogenetic relationships of nonplant GSTFs were investigated. We identified GSTFs in ascomycete fungi, myxobacteria, and protists Naegleria gruberi and Aureococcus anophagefferens. GSTF occurrence in these bacteria and protists correlated with their genome sizes and habitats. While this link was missing across ascomycetes, the distribution and abundance of GSTFs among ascomycete genomes could be associated with their lifestyles to some extent. Sequence comparison, gene structure, and phylogenetic analyses indicated divergence among nonplant GSTFs, suggesting polyphyletic origins during evolution. Furthermore, in silico prediction of functional partners suggested functional diversification among nonplant GSTFs.